Kiln drying of timber using solar energy and wood defects / Mohd Faizal Musa - Musa, Mohd Faizal (2008)
In this research wood needs to be dried first before we can use it. Solar energy is a convenient method because solar kilns give shorter drying times, produce high quality product and low operating costs compared with open-air drying and lower energy cost compared with other method kiln drying wood. This study assessed the actual performance of an instrumented industrial solar kiln and solar technology of timber. As we know, wood has quality and grade value for the market demand of sawn timber but, the various types of defects that can occur in dried wood products and to show how these defects are related to the kiln drying operation. So, we must controll the drying defects using the special drying schedule, relative humidity of wood, moisture content and the person who handle the machine must be more careful in operation solar drying in kiln dried.